On Aquinas’ Concept of Law and its Implications on Law and Lawmaking in Nigeria - Anyam, Damian Tersoo; Gbagir, Solomon Terungwa (Kashere Journal of Politics and International Relations, 2025)
It is undeniable that throughout philosophic history, the question of “what is law?” has remained contestable. From the ancient to contemporary period, there have been divergent views regarding the concept of law. To build on this intellectual discourse, St. Thomas Aquinas in his Summa Theologica formulated his theory of law. Aquinas established that law is “…an ordinance of reason for the common good, made by him who has care of the community.” In view of this understanding of law, this paper elucidates Aquinas’ concept of law in order to situate his idea of law on law and lawmaking in Nigeria. The study is a qualitative research. Data were sourced from primary and secondary sources. The paper used the expository and evaluative methods. The expository method uncovered the idea of law in Thomas Aquinas’ thought while the evaluative method examined his notion of law in order to situate its implications. The study found out that to Aquinas, law is borne out of practical reason and necessarily projects the good of everyone. It is morality toward common good. Anything short of this is unjust and not qualified to be a law. In contrast, it is been observed that in Nigeria, law and lawmaking is largely designed in a way that favours a select few so that law is served differently to different people. Regardless, Aquinas’s idea is been challenged on the basis that not all common good that are practically reasonable are morally right. However, the study concluded that Aquinas’ concept of law is considerable for law and lawmaking since it has grounds of influencing a more stable, socially, economically and ethically sound society.